5-year outcomes of salvage endoscopic nasopharyngectomy for recurrent nasopharyngeal carcinoma - Andrew Thamboo; Vishal S. Patel; Peter H. Hwang (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective Recurrent nasopharyngeal carcinoma (rNPC) can be salvaged with re-irradiation, open nasopharyngectomy, and more recently endoscopic nasopharyngectomy. However, long-term outcomes of endoscopic approaches are lacking. Thus, we report 5-year outcomes following endoscopic nasopharyngectomy for rNPC. Methods Patients who underwent endoscopic nasopharyngectomy for rNPC between January 2000 and January 2012 were retrospectively reviewed. Patients were included if they had their first endoscopic nasopharyngectomy at least 5 years prior to this study. Presenting (cTNM) status and recurrent (rTNM) status for each recurrence was determined. Outcomes included margin status, disease recurrence, death, and complication rates. Results Thirteen patients were included. Four patients had a prior open nasopharyngectomy. Mean time follow-up was 74.3 months (range = 56.4–96 months). Negative margins were achieved in 77% of initial cases. Positive margins were associated with higher rT stages. Re-recurrence was seen in 6 patients, which was also associated with a higher cStage and rStage. All patients with positive margins had re-recurrence. Four patients required repeat endoscopic nasopharyngectomy and two received chemoradiation. All four with a second endoscopic procedure had further disease recurrence. Five-year local disease-free and overall survival rates were 53.9 and 84.6%, respectively. The minor complication rate was 52.6%, major operative complication rate was 0.0%, and late complication rate was 23.1%. Conclusion Endoscopic nasopharyngectomy demonstrates promising 5-year overall survival rate for rT1 and rT2 cases of rNPC with favorable complication rates. Lower rStages were associated with a higher disease-free rate, and lower cStages were associated with improved overall prognosis. Close surveillance and prompt management of recurrences can be associated with favorable long-term tumor control. Level of evidence 4 Graphical abstract